STUDENTS' ENGLISH RESEARCH TERMINOLOGY MASTERY: DIGITAL DEPENDENCY AND LINGUISTIC CHALLENGES IN SIMEULUE - Muhammad Wiwin; Zulheri Is (CV. Abid Abadi Jaya, 2026)
This study investigates the paradoxical intersection of technological optimism and linguistic disenfranchisement among Islamic Education (PAI) students in the remote Simeulue archipelago. Utilizing a descriptive qualitative approach with 30 participants, the research identifies a critical Morphological Wall that obstructs the internalization of global research methodologies. Data triangulation through questionnaires, document analysis of proposal drafts, and semi-structured interviews reveals that 80% of students suffer from derivative affixation failure, leading to profound Meaning Hallucinations where technical terms like generalizability and operationalization are conceptually distorted. Furthermore, the study uncovers a state of Emergency Literacy driven by infrastructural stress and geographical isolation, forcing students into a Digital Determinism Trap where Artificial Intelligence (AI) is utilized as a blind